Surgical techniques in moyamoya vasculopathy : tricks of the trade - Vajkoczy, Peter (Thieme, 2020)
"In rare cases of stroke in children and youths, a likely cause is the idiopathic disease moyamoya, characterized by the slow and progressive stenosis and occlusion of the internal carotid artery and the arteries of the circle of Willis. A result of these stenoses is the formation of collaterals that are typically small and fragile, and liable to rupture. While there is no cure for moyamoya, a variety of surgical procedures can be performed to reestablish and maintain adequate blood supply to the affected brain areas. The procedures described here include various revascularization techniques and recommended bypasses"--